2012
DOI: 10.4161/hv.22414
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on the immunogenicity of paired Env immunogens from mother-to-child transmitted HIV-1 isolates

Abstract: Recent studies have reported that founder viruses play unique roles in establishing HIV-1 infection. Understanding the biological and immunological features of envelope glycoproteins (Env) from such viruses may facilitate the development of effective vaccines against HIV-1. In this report, we evaluated the immunogenicity of gp120 immunogens from two pairs of clade B and two pairs of clade C mother-to-child transmitted (MTCT) HIV-1 variants that had various levels of sensitivity to broadly neutralizing monoclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To express gp120 proteins from CHO cells, the serum-free culture supernatant of stable transfected CHO cells were collected. The harvested gp120 proteins from both 293F and CHO cells in research grade were purified using a Lectin column and verified by SDS-PAGE and Western blot analysis as previously described (20)(21)(22).…”
Section: Production Of Non-gmp Gp120 Proteinsmentioning
confidence: 99%
“…To express gp120 proteins from CHO cells, the serum-free culture supernatant of stable transfected CHO cells were collected. The harvested gp120 proteins from both 293F and CHO cells in research grade were purified using a Lectin column and verified by SDS-PAGE and Western blot analysis as previously described (20)(21)(22).…”
Section: Production Of Non-gmp Gp120 Proteinsmentioning
confidence: 99%
“…The cellular responses were also found in NHPs, and importantly, antigen-specific CD8+ Granzyme B+ T cells could be detected. An alternative approach by Lu and colleagues showed that priming with DNA vaccines followed by protein boost vaccination regimes results in remarkable immune responses [Vaine et al 2008; Wang et al 2012], but this approach gives up some of the advantages of a DNA vaccination only. Against this background of advances in the DNA vaccine field, the recent failure of Allovectin-7 [Bedikian et al 2010], a bicistronic plasmid encoding human leukocyte antigen (HLA)-B7 and β2 microglobulin formulated with a cationic lipid system, to meet its primary endpoint to achieve durable responses in advanced melanoma in a phase III trial came as a disappointment, but detailed results of the study have not yet been published (http://www.vical.com/).…”
Section: Dna Vaccinesmentioning
confidence: 99%